Decoding Transcriptome Dynamics of Genome-Encoded Polyadenylation and Autoregulation with Small-Molecule Modulators of Alternative Polyadenylation. Issue 12 (20th December 2018) - Araki, Shinsuke; Nakayama, Yusuke; Sano, Osamu; Nakao, Shoichi; Shimizu-Ogasawara, Mari; Toyoshiba, Hiroyoshi; Nakanishi, Atsushi; Aparicio, Samuel
Summary: Alternative polyadenylation (APA) plays a critical role in regulating gene expression. However, the balance between genome-encoded APA processing and autoregulation by APA modulating RNA binding protein (RBP) factors is not well understood. We discovered two potent small-molecule modulators of APA (T4 and T5) that promote distal-to-proximal (DtoP) APA usage in multiple transcripts. Monotonically responsive APA events, induced by short exposure to T4 or T5, were defined in the transcriptome, allowing clear isolation of the genomic sequence features and RBP motifs associated with DtoP regulation. We found that longer vulnerable introns, enriched with distinctive A-rich motifs, were preferentially affected by DtoP APA, thus defining a core set of genes with genomically encoded DtoP regulation. Through APA response pattern and compound-small interfering RNA epistasis analysis of APA-associated RBP factors, we further demonstrated that DtoP APA usage is partly modulated by altered autoregulation of polyadenylate binding nuclear protein-1 signaling. Graphical Abstract: Highlights: Highly potent small molecules (T4 and T5) that modulate APA are identified T4 and T5 promote distal-to-proximal APA usage in multiple transcripts Longer vulnerable introns are preferentially affected by distal-to-proximal APA Compounds target a distinctive A-rich region via autoregulated PABPN1 signaling Abstract : Araki et al. report that small molecules influence distal-to-proximal APA usage, including a distinctive A-rich region. Isolated responsive APA events define genomic sequence features and RBP motifs including PABP.